Death in Winterreise : Musico-Poetic Associations in Schubert's Song Cycle - Suurpää, Lauri, 1964- (Book collections on Project MUSE., 2014)
Lauri Suurpää brings together two rigorous methodologies, Greimassian semiotics and Schenkerian analysis, to provide a unique perspective on the expressive power of Franz Schubert's song cycle. Focusing on the final songs, Suurpää deftly combines textual and tonal analysis to reveal death as a symbolic presence if not actual character in the musical narrative. Suurpää demonstrates the incongruities between semantic content and musical representation as it surfaces throughout the final songs. This close reading of the winter songs, coupled with creative applications of theory and a thorough history of the poetic and musical genesis of this work, brings new insights to the study of text-music relationships and the song cycle.